Lecturer Mastery Level as an Indicator of Student Satisfaction Assessment - Bawono, Icuk Rangga; Setyadi, Erwin; Rahayu, Apriani Kartika (Jurnal Pendidikan Indonesia, 2021)
The development of the era demands the development of a better and less pragmatic and simplistic mindset and way of teaching in conveying science to its students. The university should now be able to change its paradigm as a site like a company engaged in services offering better service to its customers. It is a quantitative research using a questionnaire model. It analyzes the influence of lecturer competency on student satisfaction levels both directly and through the quality dimensions of services. It also analyzes the most dominant competencies as lecturer competencies. The conclusions that can be drawn from the holding of this research is the ability of the lecturer has an important influence on student satisfaction, the lecturer ability has a significant impact on the level of student satisfaction through the dimension of service quality. Meanwhile, social competence has the most dominant role in shaping the lecturer's competence. It is expected that the results of this study can be considered by lecturers so that they can always develop themselves in order to function more fully.